Leukocyte- and Platelet-Rich Fibrin (L-Prf) Obtained from Smokers and Nonsmokers Shows a Similar Uniaxial Tensile Response in Vitro - Garcia-Herrera, C; Bezmalinovic-Colleoni, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
We evaluated and compared the biomechanical properties of Leukocyte-and Platelet Rich Fibrin L-PRF clots and membranes derived from smoker and nonsmoker donors. Twenty venous-blood donors (aged 18 to 50 years) were included after signing informed consent forms. L-PRF clots were analyzed and then compressed to obtain L-PRF membranes. L-PRF clot and membrane samples were tested in quasi-static uniaxial tension and the stress–stretch response was registered and characterized. Furthermore, scanning electron microscope representative images were taken to see the fibrin structure from both groups. The analysis of stress–stretch curves allowed us to evaluate the statistical significance in differences between smoker and nonsmoker groups. L-PRF membranes showed a stiffer response and higher tensile strength when compared to L-PRF clots. However, no statistically significant differences were found between samples from smokers and nonsmokers. With the limitations of our in vitro study, we can suggest that the tensile properties of L-PRF clots and membranes from the blood of smokers and nonsmokers are similar. More studies are necessary to fully characterize the effect of smoking on the biomechanical behavior of this platelet concentrate, to further encourage its use as an alternative to promote wound healing in smokers. © 2023 by the authors.